Ganjar Pranowo’s Storytelling and Political Image on Social Media - Muksin, Nani Nurani; Sinaga, Astriana Baiti; Hidayat, Hendra; Handoko, Daniel; Shabana, Amin (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
Politics is not socially empty. Therefore, politicians must also find the right strategy to increase popularity and electability. One way that can be used is the use of social media. Social media is now widely used by political actors as a means to absorb aspirations in the political field. One of the social media that is currently widely used as a political tool is TikTok. As of April 2022, there are 99,072,000 TikTok users in Indonesia or 51.1% of the Indonesian population aged 18 years and over. This article aimed to explore how Ganjar Pranowo built his self-image through his TikTok account @ganjarpranowofc and what storytelling strategies were used in that image. A qualitative approach with a content analysis method is used in writing this article. There are 252 videos from the TikTok account @ganjarpranowo were analyzed from January to May 2022. This article uses the political image category approach described in Liebhart and Bernhardt's research (2017) as a basis for analysis. From this research, Ganjar Pranowo simplifies political issues in his imagery efforts. In addition, there are indications of three storytelling strategies used in political imagery on the TikTok account: the biographical strategy, the incumbent strategy, and the Kagama chairman strategy.